Multifunctional metal composite textile shields against electromagnetic radiation—effect of various parameters on electromagnetic shielding effectiveness. Issue 2 (15th May 2015) - Šafářová, Veronika; Militký, Jiří
Abstract : Over the last few years, there has been mounting concern about the possibility of adverse health effects resulting from exposure to radiofrequency electromagnetic fields, such as those emitted by wireless communication devices. For the reason given above, a demand for protection of human beings against influence of electromagnetic signals and troublesome charges, has been increasing. Therefore textile structures with increased electromagnetic shielding ability, which satisfy the requirements for casual dress or preserve air circulation at workplace, is suitable. This article presents the present state of fabrication and characterization of multifunctional light weight flexible fabrics with increased resistance to electromagnetic radiation while preserving basic properties of textile structures designated for clothing or technical purposes. In this article, an effect of metal content, a placement of conductive yarn, geometry, moisture content and correlation with frequencies is studied. In addition, percolation thresholds are identified and a form of relation between conductive component and total shielding effectiveness is proposed. POLYM. COMPOS., 38:309–323, 2017. © 2015 Society of Plastics Engineers